Design of Digital Targets for Slingshot Using the Quality Function Deployement (QFD) - Himawan Wismanadi; Mochammad Purnomo; Bhekti Lestari; Muhammad Labib Siena Ar Rasyid; Laurentino Guterese (Faculty of Sport and Health Sciences, 2024)
The research aims to determine user criteria regarding digital slingshot targets using the Quality Function Deployment (QFD) method based on ergonomic tool design. This type of research is a case study research conducted through questionnaires. 38 respondents from East Java Indonesian Traditional Slingshot Association (PERKATIN) filled out a questionnaire consisting of 11 questions. Based on the weight of relative importance, the attribute priority results are color variations (12.57), material economic life (12), ease of operating the tool (12), material strength (11.57), choice of tool shape (11.08). The conclusion is that the priority consistently includes the attributes of color variations, material economic life, ease of operating the tool, material strength, and choice of tool shape in determining the user criteria of the digital target tool slingshot as needed.